BNPL in the Consumerism World: About the Excessive Debt Trap - Bagniewski, Bartosz; Kubiczek, Jakub; Żuchowska, Zuzanna (Journal of Finance and Financial Law, 2024)
The purpose of the article. This article aims to present the characteristics of BNPL and the excessive debt risk it poses within the context of widespread consumerism. Methodology. The study relies on secondary data obtained through a thematic literature review, encompassing scientific publications and industry reports. Focusing on the Polish BNPL market, the research synthesizes this information to outline BNPL’s operational characteristics, identify determinants influencing Polish consumers' adoption of BNPL, and discuss both the prospects and risks associated with BNPL usage. Results of the research. Findings indicate that BNPL facilitates consumer purchases by deferring payments, which can drive consumerism and increase the inclination to use BNPL, thus accelerating its growth. The simplicity and convenience of BNPL, coupled with the absence of immediate financial repercussions, can lead to irresponsible usage and push consumers into an excessive debt trap. Additionally, a lack of economic knowledge, particularly financial literacy, further heightens the risk of a debt spiral. In the context of broader discussions on BNPL, other significant risks must be considered, as the expansion of these services depends on meeting expectations similar to those of other digital lending options. This includes establishing consumer trust in BNPL, largely through mitigating such risks. Like other digital services, BNPL requires the sharing of personal data, introducing potential security concerns. Therefore, BNPL providers must prioritize data protection to secure consumer information. Additionally, consumers should stay cautious to avoid fraud, like phishing, by being aware of the risks.